Green Synthesis and Electrochemical Properties of Mono- and Dimers Derived from Phenylaminoisoquinolinequinones - Ibacache-Rojas, J; Faundes-Anazco, J (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
In the search for new quinoid compounds endowed with potential anticancer activity, the synthesis of novel heterodimers containing the cytotoxic 7-phenylaminoisoquinolinequinone and 2-phenylaminonaphthoquinone pharmacophores, connected through methylene and ethylene spacers, is reported. The heterodimers were prepared from their respective isoquinoline and naphthoquinones and 4,40-diaminodiphenyl alkenes. The access to the target heterodimers and their corresponding monomers was performed both through oxidative amination reactions assisted by ultrasound and CeCl3-7H2Ocatalysis "in water". This eco-friendly procedure was successfully extended to the one-pot synthesis of homodimers derived from the 7-phenylaminoisoquinolinequinone pharmacophore. The electrochemical properties of the monomers and dimers were determined by cyclic and square wave voltammetry. The number of electrons transferred during the oxidation process, associated to the redox potential EI1/2 , was determined by controlled potential coulometry. © 2019 by the authors.